Strategi Kreatif Pesan Iklan Brimo Edisi Septian David Maulana - Yessi Mareta Andari Putri (LPPM Universitas Pramita Indonesia, 2022)
The habits of consumers in the digital era encourage advertisers to innovate to make more creative advertisements so that product messages can be conveyed effectively and efficiently to the public. BRImo's latest advertisement uses professional soccer players in the Liga 1 competition and Indonesian National Football team players Septian David Maulana and sportcaster Valentino Simanjuntak as voice overs. creative messages from football players and sportscasters into a strategy to sell products to consumers. Ads are made funny in order to attract the attention of the audience. the semiotic method is used to see the signs in the Septian David Maulana edition of BRImo's advertisement.